Atypicality and Accountability: Evidence from Five Experiments - Betancourt, Nathan; Hoever, Inga J.; Wezel, Filippo Carlo (Organization Science, 2025)
This paper investigates the interactive effect of organizational atypicality and accountability on evaluation. Prior research has shown that audience members sometimes react positively and other times negatively to atypical organizations or that the main effect of atypicality is not always consistent. We seek to further advance our understanding of this inconsistency in the assessment of atypical organizations. To do so, we focus on accountability, defined as a person’s expectation that they may be asked to justify their choices to others. We theorize that accountability will influence the assessment of atypical organizations because it causes evaluators to think about justifying their decisions and considering what their audience will find acceptable. We investigate two different ways in which accountability, by making others’ social expectations salient, shapes the effect of atypicality on appeal. First, when the preferences of the evaluator’s audience are implicit, we propose that accountability will strengthen the negative effect of atypicality on evaluation. Second, when the preferences of the evaluator’s audience are explicit, we propose that evaluators will conform to these preferences. When an evaluator is accountable to an audience that prefers typical organizations, atypicality will negatively affect evaluation. Conversely, when an evaluator is accountable to an audience that prefers atypical organizations, atypicality should positively affect evaluation. We tested these predications in five preregistered studies and found support for our predictions. These results help to explain variance in audience member’s reactions to atypicality and suggest that accountability plays a fundamental role in the evaluation of atypical organizations. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2022.16937 .